Engagement in a newly launched online support community for complex regional pain syndrome: membership growth, header analysis and introductory messages. (2016) - Smedley, Richard M.; Coulson, Neil S.; Gavin, Jeff; Rodham, Karen; Watts, Leon
Several studies have investigated forum engagement, with a small but growing body of research focusing on the number of people using a forum (membership growth), how they use it (header analysis) and how they introduce themselves (introductory messages). Most studies use established forums and little is known about newly launched forums. This study examines engagement in a newly launched forum for complex regional pain syndrome. Results showed that membership growth occurred in bursts that were closely linked to promotional strategies. Header analysis showed the forum was used throughout the day, evening and night, with a focus on providing support as well as receiving it. Introductory messages took the form of disease stories with six themes: personal details, precipitating event, symptoms, treatment, living with CRPS, and reasons for joining. Implications and areas for future research are discussed.